Penerapan Akuntansi Pondok Pesantren (Studi pada Toko Pondok Pesantren Sengkubang) - Wulan Wahyu Ningrum (Aktiva, 2023)
Purpose: This study aims to find out how prepared the Islamic boarding school shop is to manage finances and to inform about the feasibility of financial management in the Sengkubang Islamic Boarding School shop. Design/methodology/approach: This study uses descriptive qualitative method, data collection techniques with documentation, observation, and interviews with the Islamic boarding school. Research Findings: The application of accounting in the Sengkubang Islamic Boarding School shop cannot be said to be perfect, but it is feasible to be used as financial information. Contribution/Originality/Novelty: Can be used as an evaluation material for the shop management of the Sengkubang Islamic Boarding School in improving the application of Islamic boarding schools accounting.